Transference of some microsatellite molecular markers from Fabaceae family to Andean Lupin (Lupinus mutabilis Sweet) - Chirinos-Arias, Michelle C. (2015)
In order to analyze transferibility of 15 microsatellite primers from Fabaceae family to Lupinus mutabilis Sweet "andean lupine" chosen to present transferability between species and genera, by its high rate of polymorphic content (PIC) and high degree of observed and expected heterozygosity. DNA was extracted of 300 andean lupines plants, PCR conditions were standardized by gradients of master mix components. Primers for screening were run on 3% agarose gel with some samples. Finally population was amplified and run on 6% polyacrylamide gel for its highest resolution. Only 6.67% of primers were amplified, but they were monomorphic, so they cannot be used for molecular characterization. We proposed eight microsatellite primers for andean lupin wich should be probed in laboratory conditions.